Overlapping dialogues: the role of interpretation design in communicating Australia’s natural and cultural heritage - Woodward, Margaret (Curtin University, 2009)
This research investigates the development of interpretation design in Australia during the period 1980 – 2006, and its role in presenting natural and cultural heritage to audiences in visitor settings. It establishes Australian interpretation design at the intersection of two professional fields, interpretation and design. Where heritage interpretation originates from a background of spoken language, through narrative and storytelling, graphic and communication design have origins in visual language, communicated through images and text. This research positions interpretation design as a new field within design and traces its emergence as a hybrid of spoken and visual traditions of communication.The study gives visibility to this previously undocumented and un-theorised hybrid field of design and creates a thematic conceptual framework within which to locate its historical, conceptual and practical origins. In substantiating interpretation design as a new field, three avenues of enquiry were considered; documentation and analysis of the visual artefacts of interpretation design, locating interpretation design in a wider conceptual and professional context through literature reviews, and consultation with designers in order to understand the challenges and problems in this new mode of design. Further, to facilitate designers to continue to work effectively in highly collaborative, complex and cross-disciplinary professional environments a conceptual collaborative tool was developed for use by interpretation design project teams. The conceptual tool integrates the theoretical and practical findings from this research and is based on a pattern language approach first developed by Christopher Alexander et al (1977).The research is conducted from a design perspective, and integrates theoretical and professional knowledge from related fields into interpretation design practice. Through a progressively widening interrogation of the literature, professional contexts, and designed artefacts of interpretation design, this new area of design is examined from a number of perspectives, building up a multi-faceted framework for understanding its historical, conceptual and practical dimensions. A Grounded Theory methodology was adapted to develop the theoretical framework of this study and to gather a wide range of relevant data. The practical outcome of the research was developed using a Pattern Language methodology originating from a problem-based design approach in architecture (Alexander et al 1977) and underpinned the interpretation of data.Conclusions of the research found that despite invisibility within the discourse of Australian design, designers working in this specialised field of practice have, since the early 1980s, contributed to projects which shape ideas, attitudes and visual representations of natural and cultural heritage in Australia’s most widely visited and valued sites. Designer’s practice is identified as part of an ongoing process of both contributing to Australian cultural narrative and being influenced by the legacy of culture. Contemporary interpretation design is highly cross-disciplinary and collaborative, characterised by a differentiated professional practice with dispersed networks of stakeholders. While interpretation design is located within a larger framework of the professional practice of interpretation, there exists many opportunities to enrich and better inform designers by integrating wider pools of knowledge that intersect the activities of interpretation, including education, tourism, visitor studies and psychology.